Corporate liability for modern slavery. Issue 2 (11th October 2021) - Bakirci, Kadriye; Ritchie, Graham
Abstract : Purpose: The purpose of this paper is to provide an overview of evolving developments in international, regional and EU law including the UK and Turkish jurisdictions for the liability of corporate businesses for modern forms of exploitative labour practices described as the modern forms of slavery. Design/methodology/approach: In the first part, this paper outlines international, regional and EU instruments, UK and Turkish jurisdictions in relation to modern forms of slavery. The second part reviews legal frameworks for corporate liability for modern forms of slavery. Findings: Slavery, slavery-like practices or some other exploitative practices are prohibited by numerous international law instruments starting from 1904. Apart from old forms of defined exploitative practices, multiple relevant current exploitative practices, called contemporary or modern forms of slavery exist all over the world. Under various international or regional conventions signatory States have been held responsible for exploitative practices by the international or regional courts or supervisory bodies, yet businesses were largely overlooked as a participating partner in the global movement to eradicate modern forms of slavery. For many years, multi-national businesses have engaged with various voluntary international corporate social responsibility initiatives in response to demands to operate in a socially responsible manner. There is a growing global recognition of the role corporate businesses can and should play in tackling crime and exploitative practices. A number of initiatives at the international and EU level and the introduction of the California Transparency in Supply Chains Act, (2010 – effective from 2012), the UK Modern Slavery Act 2015, the French Act on Due Diligence of Corporations and Main Contractors 2017 (loi sur le devoir de vigilance), the Australian Commonwealth Modern Slavery Act 2018, the Dutch Child Labour Due Diligence Act 2019, (which is due to come into effect in mid-2022), reflect this recognition. Originality/value: This paper argues that it is important for companies to use available tools, participate in joint initiatives and advocate for binding international and regional instruments and effective national legislation and action – all aimed at ending business involvement in modern forms of slavery.